Tersangka, Terdakwa, Terpidana dalam Perspektif Perilaku - Adinda Zahra Septiany Rusdiono; Fadillah Nurul Fitriani; Hendra Rizki Taruna; Putri Adelia Anjani; Tugimin Supriyadi (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
In the legal world, suspect, accused and convict are terms that have meaning. Legal protection is a form of effort to protect society from arbitrary actions by covering several important aspects aimed at ensuring a fair process is obtained. Based on what is stated in Article 1 Number 14 of the Criminal Procedure Code regarding those who are called suspects, Article 1 Number 15 of the Criminal Procedure Code for those who are declared defendants and Article 1 Number 32 of the Criminal Procedure Code regarding those who are declared convicts. This research uses a literature review method by exploring various literature related to the research topic.